Are Men at Greater Risk of Lean Mass Deficits in Rheumatoid Arthritis?1. Issue 1 (January 2015) - Baker, Joshua F.; Long, Jin; Ibrahim, Said; Leonard, Mary B.; Katz, Patricia
<x xml:space="preserve">Abstract</x> Objective We aimed to determine if there were sex differences in lean body mass (LBM) in patients with rheumatoid arthritis (RA) when compared with sex‐ and race‐specific National Health and Nutrition Examination Survey (NHANES) reference data, and to investigate the impact of sex differences in risk factors for LBM deficits. Methods Dual x‐ray absorptiometry measures of whole body LBM and appendicular LBM (arms and legs, appendicular lean mass [ALM]) were obtained on a total of 190 subjects from 2 independent cohorts (141 from San Francisco [SF], 49 from Philadelphia [PA]), expressed as indices adjusted for height (LBM index and ALM index, kg/m2), and converted to sex‐ and race‐specific Z scores relative to age and based on NHANES data. Sarcopenia was defined using 4 different sex‐specific definitions. Multivariable linear and logistic regression analyses adjusted for disease activity, disease duration, physical activity, anti–cyclic citrullinated peptide seropositivity, fat mass index, and glucocorticoid use. Results While there were significant differences between the 2 cohorts, ALM index Z scores were significantly lower in men compared to women in both (SF: −1.43 versus −0.43, P < 0.0001; PA: −0.83 versus −0.06, P = 0.03). Observed sex differences were significant after adjustment in multivariable analyses within both cohorts. Odds of sarcopenia were 3 to 8 times greater in men in the SF cohort. Men in the PA cohort also had a higher, but nonsignificant, risk of sarcopenia. Conclusion RA is associated with significant LBM deficits, with greater deficits observed in men. Future study may help elucidate the mechanisms driving greater deficits among men.